Pengaruh Koneksi Politik dan Mekanisme Corporate Governance Terhadap Biaya Audit - Stefi Febrianti; Yeterina Widi Nugrahanti (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the impact of political connections and corporate governance mechanisms on audit fees. The mechanism of corporate governance in this study is seen from the roles of the board of commissioners, board of directors and audit committee. The data used in this study is secondary data, namely the annual reports of manufacturing companies listed on the Stock Exchange for the period 2018-2020. The sampling technique used in this study was purposive sampling and based on the criteria obtained as many as 432 manufacturing companies. Hypothesis testing was carried out using multiple regression analysis. The results of this study reveal that political connections have a positive effect on audit fees. Other results also reveal that the Independent Board of Commissioners, Audit Committee, and Institutional Ownership variables have a negative effect on audit fees.